Spiritual parenting : an awakening for today's families - Anthony, Michelle (Colorado Springs, CO : David C. Cook, 2010)
Parents are, by the power of God's Spirit, to depend on God in order to create home environments that God can use to beckon our kids to Him. It's it time to embrace this simple but revolutionary concept?
In the path of the divine: beyond managing behavior -- What's the rock?: a transforming faith -- A garden and a big white horse: the environment of storytelling -- Royal blood: the environment of identity -- Help from our friends: the environment of the faith community -- What needs to be done?: the environment of service -- A heart of dependence: the environment of out of the comfort zone -- An entrusted kingdom: the environment of responsibility -- Discipline that heals: the environment of course correction -- Down at eye level: the environment of love and respect -- A true relationship: the environment of knowing -- What is say is what I do: the environment of modeling.
Includes bibliographical references.
Keywords: Parenting -- Religious aspects -- Christianity; Christian life